Characterization of Patients With Obstructed Defecation and Slow Transit Constipation With a Simulated Stool. Issue 5 (5th May 2021) - Gregersen, Hans; Chen, Ssu-Chi; Leung, Wing Wa; Wong, Cherry; Mak, Tony; Ng, Simon; Daming, Sun; Futaba, Kaori
Abstract : INTRODUCTION: Defecatory disorders including obstructed defecation (OD) are currently diagnosed using specialized investigations including anorectal manometry and the balloon expulsion test. Recently, we developed a simulated stool named Fecobionics that provides a novel type of pressure measurements and analysis. The aim was to study OD phenotypes compared with slow transit constipation (STC) patients and normal subjects (NS). METHODS: Fecobionics expulsion parameters were assessed in an interventional study design. The Fecobionics device contained pressure sensors at the front, rear, and inside a bag. All constipation patients had colon transit study, defecography, anorectal manometry, and balloon expulsion test performed. The Fecobionics bag was distended in the rectum until desire-to-defecate in 26 OD compared with 8 STC patients and 10 NS. Rear-front pressures (preload-afterload parameters) and defecation indices (DIs) were compared between groups. RESULTS: The Wexner constipation scoring system score was 13.8 ± 0.9 and 14.6 ± 1.5 in the OD and STC patients ( P > 0.5). The median desire-to-defecate volume was 80 (quartiles 56–80), 60 (54–80), and 45 (23–60) mL in OD, STC, and NS, respectively ( P < 0.01). The median expulsion duration was 37 (quartiles 15–120), 6 (3–11), and 11 (8–11) seconds for the 3 groups ( P < 0.03). Fecobionics rear-front pressure diagrams demonstrated clockwise loops with distinct phenotype differences between OD and the other groups. Most DIs differed between OD and the other groups, especially those based on the anal afterload reflecting the nature of OD constipation. Several OD subtypes were identified. DISCUSSION: Fecobionics obtained novel pressure phenotypes in OD patients. DIs showed pronounced differences between groups. Larger studies are needed on OD subtyping.